Self-heating behavior and ignition of shale rock - Restuccia,F; Ptak,N; Rein,G (Combustion and Flame, 2016)
The combustion of shale, a porous sedimentary rock, has been reported at times in outcrop deposits and piles. However, the initiating event of most of these fires is unknown. It could be that, under the right conditions, shale rock undergoes spontaneous exothermic reactions in the presence of oxygen. This work studies experimentally and for the first time the self-heating behavior of shale rock. As shale has high inert content, novel diagnostics such as mass loss measurements and observation ofcharring are introduced to the self-heating ignition criteria in respect to other self-heating materials.Using field samples collected from the outcrop at Kimmeridge Bay (UK) and the Frank-Kamenetskii theory of ignition, we determine the effective kinetic parameters for two particle-size distributions of shale. These parameters are then used to upscale the results to geological deposits and mining piles of different thicknesses. We show that for fine particles, with diameter below 2 mm, spontaneous ignition is possible for deposits of thickness between 10.7 m and 607 m at ambient temperatures between -20 C and 44 C. For the same ambient temperature range, the critical thickness is in excess of 30 km for deposits made of coarse particles with diameter below 17 mm. Our results indicate that shale rock is reactive, with reactivity highly dependent on particle diameter, and that self-ignition is possible for small particles in outcrops, piles or geological deposits accidentally exposed to oxygen.